Use of secret simulated patient followed by workshop based education to assess and improve inhaler counseling in community pharmacy in Jordan - Elayeh ER; Hammad EA; Tubeileh RH; Basheti IA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Objectives: To assess inhaler technique demonstration skills of community pharmacists located in Amman, Jordan via incorporating the trained secret simulated patient (SSP) approach. Secondly, to evaluate the effectiveness of a 2-hour educational workshop focused on SSP feedback. Methods: This cross-sectional study involved community pharmacies located in Amman, Jordan. Initially, a trained SSP was involved to enact baseline visits requesting advice on how to use Ventolin® (a pressurized metered-dose inhaler; pMDI) and Pulmicort® (a Turbohaler inhaler, TH). Immediately after each visit, the SSP completed an inhaler technique evaluation form with inhaler checklists based on previously published checklists (consisting of 9 and 10 items for pMDI and TH respectively). The SSP invited all participating pharmacists to a 2-hour workshop that included feedback on their demonstration skills, and the second evaluation of their inhaler technique. The workshop included a summary of the initial visits' results highlighting pharmacists' performance. Results: Sixty pharmacies were visited and 120 inhaler assessments were completed. During baseline assessment, pharmacists scored an average of 4.5 out of 9 for pMDI and 4.9 out of 10 for TH. Only 11 pharmacists (18.3%) attended the workshop. During the workshop, inhaler technique demonstration skills significantly improved, as scores improved from 5.4 (SD 1.6) to 7.8 (SD 0.9) (p=0.008) and from 4.6 (SD 2.5) to 9.9 (SD 0.6) (p=0.003) for pMDI and TH respectively. Conclusions: The SSP approach revealed a lack of ability to demonstrate correct inhaler technique for pMDI and TH inhalers by community pharmacists in Amman, Jordan. A focused educational workshop based on SSP feedback improved inhaler technique significantly.